Family Medicine in Undergraduate Medical Education in India - Sankarapandian, Venkatesan (J Family Med Prim Care, 2014)
The Medical Council of India has set appropriate and relevant objectives to train each medical student into a basic doctor for the country. Even though they envisage that these basic doctors would work as physicians of first contact, providing for the health needs of India at primary and secondary care level, the site of training and the context of clinical teaching do not seem to empower the students to become a basic doctor. ‘Vision 2015’, the document written by the board of governors of medical council of India suggests reforms in medical education such as early clinical exposure, integration of principles of family medicine, and clinical training in the secondary care level. Family medicine training with trained family medicine faculty might add this missing ingredient to our basic doctor training. This article discusses the role of family medicine in undergraduate medical training. We also propose the objectives of such training, the structure of the training process, and the road blocks with possible solutions to its implementation.